Ladu Arai Pinang dari Makanan Tradisional Menjadi Komoditas Oleh-Oleh Khas Kota Pariaman - Novia Maullyyana Putri; Najmi Najmi (Jurusan Sejarah FIS UNP, 2026)
This study analyzes the transformation of Ladu Arai Pinang from traditional food into a souvenir commodity in Pariaman City during 2010–2024. It employs a historical method with a qualitative approach through heuristics, source criticism, interpretation, and historiography. Data were collected through interviews, documentation, and literature review. The findings show that Ladu Arai Pinang was originally a household food and part of socio-cultural activities. Its transformation since 2010 was not merely a culinary product change, but a historical process in which tourism growth, migrant mobility, and household economic needs turned family-based traditional food into a market-oriented souvenir while preserving its identity. Commercialization was marked by increased production scale, flavor innovation, modern packaging, broader distribution, and social media marketing. Despite commodification, producers maintained the traditional shape, name, and recipe as cultural markers of Pariaman. The transformation was shaped by tourism development, economic pressure, changing consumption preferences, technological advancement, and social networks. This perspective places local cuisine as evidence of social and economic change in a coastal community. This study concludes that Ladu Arai Pinang represents cultural adaptation within a coastal city economy without losing its traditional values.